Contraceptive use intentions and unmet need for family planning among reproductive-aged women in the Upper East Region of Ghana - Bawah, A.A.; Asuming, P.; Achana, S.F.; Kanmiki, E.W.; Awoonor-Williams, J.K.; Phillips, J.F. (Reproductive Health, 2019)
Background:Motivations for use of contraceptives vary across populations. While some women use contraceptivesfor birth spacing, others adopt contraception for stopping childbearing. As part of efforts to guide the policyframework to promote contraceptive utilization among women in Ghana, this paper examines the intentions forcontraceptive use among reproductive-aged women in one of the most impoverished regions of Ghana.Methods:This paper utilizes data collected in 2011 from seven districts in the Upper East Region of northernGhana to examine whether women who reported the use of contraceptives did so for the purposes of stopping orspacing childbirth. A total of 5511 women were interviewed on various health and reproductive health relatedissues, including fertility and family planning behavior. Women were asked if they would like to have any morechildren (for those who already had children or those who were pregnant at the time of the survey).Results:The prevalence of contraceptive use was low at 13%, while unmet need is highly pervasive and demandfor family planning is predominantly for spacing future childbearing rather than for the purpose of stopping.Overall, about 31.7%of women not using contraceptives reported a need for spacing while 17.6% expressed a needfor limiting. Thus, the latent demand for family planning is dominated by preferences for space rather than limitingchildbearing.Conclusion:Results show that there is latent demand for family planning and therefore if family planningprograms are appropriately implemented they can yield the desired impact.
Keywords: Contraception; Unmet need, birth spacing; Family planning; Reproductive health; Fertility